Critical Care Nutrition Therapy for Non-nutritionists (Springer International Publishing, 2018)
This book offers a pragmatic approach to day-to-day metabolic and nutritional care based on physiological considerations. Due to the numerous controversial trials published in the last 15 years, there is no clear guidance for intensive care physicians regarding the metabolic and nutritional management of patients. This has resulted in a return to underfeeding and related complications in most ICUs worldwide as shown by the latest Nutrition Day data. Using a structured, logical approach, the book examines practical solutions for artificial feeding in complex areas of critical care (brain injuries, burns, cardiac failure, ECMO, intestinal failure, long term patient, renal failure, metabolic diseases, obesity, old patients) and discusses measurement of the results of metabolic interventions. It also includes dedicated chapters focusing on specific problems, in order to avoid complications. Critical Care Nutrition Therapy for Non-nutritionists is a valuable resource for all general ICUs and ICU subspecialties such as cardiovascular, neuro, gastrointestinal and burns ICUs.